Genetic Subtraction Profiling Identifies Candidate miRNAs Involved in Rice Female Gametophyte Abortion. Issue 7 (1st July 2017) - Yang, Liyu; Wu, Ya; Wang, Wenliang; Mao, Bigang; Zhao, Bingran; Wang, Jianbo
Abstract: The female gametophyte is an important participant in the sexual reproduction of plants. The molecular mechanism of its development has received much attention in recent years. As important regulators of gene expression, miRNAs have been certified to play a significant role in many biological processes of plants, including sexual reproduction. In this study, to investigate the potential regulatory effects of miRNAs on rice female gametophyte abortion, we used the high-throughput sequencing method to compare the miRNA transcriptome in ovules of a high frequency female-sterile line ( fsv1 ) and a rice wild-type line (Gui 99) during ovule development. As a result, 522 known miRNAs and 295 novel miRNAs were expressed in the developing ovule of rice, while 100 known miRNAs were significantly differentially expressed between these two rice lines during ovule development. Combining with gene expression information, a total of 627 coherent target genes of these differential expressed known miRNAs between fsv1 and Gui 99 were identified. The functional analyses of these coherent target genes revealed that the coherent target genes of differential expressed known miRNAs between the two rice lines are involved in many biological pathways, such as protein degradation, auxin signal transduction, and transcription factor regulation. These results provide us with important clues to investigate the regulatory roles of miRNAs in rice female gametophyte abortion.